2021
DOI: 10.1111/gcb.15957
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term monitoring indicates shifting fall migration timing in monarch butterflies (Danaus plexippus)

Abstract: The North American monarch butterfly (Danaus plexippus) is renowned for its annual multigenerational migration cycle. Every fall, individuals east of the Rocky Mountains travel up to 4300 km from their summer breeding range across the northern United States and southern Canada to central Mexico, where millions of butterflies aggregate at high densities in high-altitude oyamel fir (Abies religiosa) forests to overwinter (Calvert & Brower, 1986). However, declining populations observed in overwintering grounds h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 48 publications
1
22
3
Order By: Relevance
“…Meanwhile Ethier (2020) examined temporal trends in migrating monarch abundance for the southern Ontario region, and concluded there was no recent decline in the annual migratory cohort there, which is at the beginning of the migratory journey. Similarly, Culbertson et al (2021) found no evidence of declines over 30 years in the number of migrating monarchs in the Atlantic coast region. Our analysis considering NABA counts from the entire breeding population suggests that monarchs may have some ability to rebound from winter declines during the breeding season, perhaps providing some counteracting upward movement of monarch numbers despite declines in the winter.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Meanwhile Ethier (2020) examined temporal trends in migrating monarch abundance for the southern Ontario region, and concluded there was no recent decline in the annual migratory cohort there, which is at the beginning of the migratory journey. Similarly, Culbertson et al (2021) found no evidence of declines over 30 years in the number of migrating monarchs in the Atlantic coast region. Our analysis considering NABA counts from the entire breeding population suggests that monarchs may have some ability to rebound from winter declines during the breeding season, perhaps providing some counteracting upward movement of monarch numbers despite declines in the winter.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, Culbertson et al (2021) found no evidence of declines over 30 years in the number of migrating monarchs in the Atlantic coast region. Our analysis considering NABA counts from the entire breeding population suggests that monarchs may have some ability to rebound from winter declines during the breeding season, perhaps providing some counteracting upward movement of monarch numbers despite declines in the winter.…”
Section: Re Sultsmentioning
confidence: 84%
“…The fall migrations in the month of September and October are delayed by six days per decade, due to the high temperatures in these two months. This led to a decrease in the arrival of migratory numbers to winter sites in Mexico, which in turn affected the success of their migration and thus the destruction of these species (Culbertson et al, 2022). Studies indicated that the climate works in conflicting ways during the spring and summer.…”
Section: The Impact Of Global Warming On Butterflies and Their Migrationmentioning
confidence: 99%
“…Our analysis therefore explores various aspects of temperature and precipitation in the months leading up to fall migration to untangle their relative influence on several metrics of fall migration timing. Climate metrics used for phenological studies are frequently aggregated monthly to assess their effects on flight timing in butterflies (e.g., Culbertson et al, 2021;Zipf et al, 2017). We adopt this approach for comparative purposes (herein, the monthly climate average analysis).…”
Section: Introductionmentioning
confidence: 99%